Character Education in a Multicultural Context: Strategies for Strengthening Values of Tolerance in Schools - Rinovian Rais; Muslimin Muslimin; Lathifah Zulty (Journal of Pedagogi, 2025)
Schools in Indonesia increasingly reflect a multicultural social reality characterized by religious, ethnic, cultural, and linguistic diversity. In this context, character education is often positioned as a key instrument for strengthening tolerance. However, character education practices are not always effective when implemented normatively and uniformly without considering the social dynamics of multicultural schools. This study aims to analyze strategies for strengthening tolerance values through character education in multicultural school settings and to explore the social and pedagogical dynamics shaping students’ tolerance. A qualitative approach was employed using in-depth interviews, participant observation, and document analysis in schools with a clear multicultural background. The findings indicate that character education is effective when implemented contextually and dialogically through the integration of tolerance values into daily learning, cross-identity social interactions, and inclusive school culture. Teachers act as value mediators, while tolerance is constructed through social negotiation rather than value indoctrination. Nevertheless, the implementation of multicultural character education faces structural challenges, including differences between family and school values, implicit bias, limited teacher capacity, and symbolic policy implementation. This study highlights the importance of reflective and adaptive approaches in character education to sustainably strengthen tolerance in multicultural school contexts.